Упростите выражение:(1/m-p - 1/m+p ):2/3m-3p /-это дробь. ДАЮ 91 БАЛ

0 голосов
75 просмотров

Упростите выражение:(1/m-p - 1/m+p ):2/3m-3p
/-это дробь.
ДАЮ 91 БАЛ


Алгебра (14 баллов) | 75 просмотров
Дано ответов: 2
0 голосов

((1*(m+p)-1*(m-p))/((m-p)*(m+p))/(2/(3*(m-p)))=((m+p-m+p)/((m-p)*(m+p))*((3*(m-p))/2)=2p/((m-p)*m+p))*((3*(m-p))/2)=3p/(m+p) (Примечание скобку(m-p) мы сократили)

(30 баллов)
0 голосов

((1*(m+p)-1*(m-p))/((m-p)*(m+p))/(2/(3*(m-p)))=((m+p-m+p)/((m-p)*(m+p))*((3*(m-p))/2)=2p/((m-p)*m+p))*((3*(m-p))/2)=3p/(m+p) (Примечание скобку(m-p) 

(106 баллов)